Sports participation on energy availability among female school athletes - Mehrulnisha Abdul, Annuar (Universiti Sains Malaysia, 2009)
Energy balance is essential for maintaining body process, so do perform well for athletes. In this study, 20 subjects from different sport (archery, athletics, fencing, golf, hockey, and netball) were carried out on individual (N=8) and team sport (N=12) group. Self-reported method was used to determine nutritional intake. Participants were provided with written and guidelines for the completion of the diaries. Physical activity details were also recorded, and used in combination with BMR prediction to calculate daily energy expenditure. Results shows energy intake was low (1806.67 ± 410 kcallday) in relation to previous recommendation for adolescents. Result shows that the energy availability of individual .· between two group with deficit average of -616.0 ± 498.5 kcallday and - 915.1 ± 400.0 kcal/day in individual and team sport respectively with the PAL in the active range (1.6-1.89). In this study we reported that both group fall below approximately 30 kcal/day of FFM. In conclusion, both group have low energy availability. If condition of low energy availability occurs for a long period of time, it can cause lots of other problem, and the most common among athletes, female athlete triad. Recommend to increase their nutritional intakes to balance with their energy expenditure.